The effects of sertraline administration from adolescence to adulthood on physiological and emotional development in prenatally stressed rats of both sexes - Pereira-Figueiredo, Inês; Sancho, Consuelo; Carro, Juan; Castellano, Orlando; López, Dolores E. (Frontiers in Behavioral Neuroscience, 2014)
Sertraline is a clinically effective Selective Serotonin Reuptake Inhibitor known to increase and stabilize serotonin levels. This neurotransmitter plays an important role in adolescent brain development in both rodents and humans, and its dysregulation has been correlated with deficits in behaviour and emotional regulation. Since prenatal stress may disturb serotoninergic homeostasis, the aim of this study was to examine the long-lasting effects of exposure to sertraline throughout adolescence on behavioural and physiological developmental parameters in prenatally stressed Wistar rats. Sertraline was administered (5mg/kg/day p.o.) from the age of 1-3 months to half of the progeny, of both sexes, of gestating dams stressed by use of a restraint (PS) or not stressed. Our data reveal that long-term sertraline treatment slightly reduced weight gain in both sexes, but reversed the developmental disturbed ‘catch-up’ growth found in PS females. Neither prenatal stress nor Sertraline treatment induced remarkable alterations in behaviour and had no effects on mean startle reflex values. However, a sex-dependent effects of PS was found: in males the PS paradigm slightly increased anxiety-like behaviour in the open field, while in females, it impaired startle habituation. In both cases, sertraline treatment reversed the phenomena. Additionally, the PS animals exhibited a disturbed leukocyte profile in both sexes, which was reversed by sertraline. The present findings are evidence that continuous sertraline administration from adolescence through adulthood is safe in rodents and lessens the impact of prenatal stress in rats.